MECHANICAL PROPERTIES OF 3D PRINTED FACIAL PROSTHESES COMPARED TO HANDMADE SILICONE POLYMER PROSTHESES - Zardawi, Faraedon M; Xiao, Kaida; van Noort, Richard; Yates, Julian M (European Scientific Journal, ESJ, 2015)
Purpose: To evaluate the mechanical properties of the 3D printed starch models infiltrated with maxillofacial silicone polymers used for fabrication of maxillofacial prostheses compared to the mechanical properties of pure silicone polymer models. Materials and methods: The test and control specimens were designed according to industry standards ASTM specifications using SolidWorks 2008 software for testing tensile strength tear strength, percentage elongation and hardness properties of starch infiltrated silicone polymer. Ten Dumbbell-shaped specimens and ten Trousershaped specimens with four hardness test specimens were printed by Zcorp 510 3D printer and infiltrated with Sil-25 maxillofacial silicone polymer. Whereas, control samples made from pure Sil-25 silicone polymers using a stainless steel mould and following a similar specification of test specimens. Lloyd LRX tensile instrument; load rating 100 N at a constant crosshead speed of 25 mm/min for testing tensile, tear strength and percentage elongation and Hardness Tester (England) was used to measure shore A durometer hardness. Results: Silicone polymer infiltrated starch (test) specimens demonstrated significantly lower tensile strength, tear strength and percentage elongation than the pure silicone polymer (control) samples (p<0.05). However, a significant increase (p<0.05) in the hardness of the printed specimens was recorded against the pure silicone samples. Conclusion: The 3D printed soft tissue prostheses – the final product showed significantly different mechanical properties compared to the handmade prostheses; they were significantly harder and reported lower mechanical properties.